The Study of Early Selection Method through Vigor and Viability Parameter in Citrus amblycarpa (Hassk) under Salinity and Drought Stress Condition - Nindita, Anggi; Umam, Choirul; Fatimah, Siti; Suwarno, Faiza (Journal of Tropical Horticulture, 2018)
The study was aimed to obtain information regarding the early selection method of Limau lime under saline and drought condition including the proper method for seed extraction, observation period in germination testing, and type of germination media. The experiment was conducted from March 2015 to January 2016 at the Laboratory of Seed Science and Technology, Department of Agronomy and Horticulture, Faculty of Agriculture, Bogor Agricultural University. It consisted of four main experiments. The first experiment was the extraction method on Limaulime seed using distilled water, ash from the husk, talcum powder, and HCl 1%. The second experiment was germination testing of lime seed using three media i.e. sand, the combination of sand: soil (1:1) (v:v), and towel tissue. The third experiment has tested the vigor of Limau lime seeds in different saline conditions by using NaCl, i.e. 1500 ppm, 3000 ppm, and 4500 ppm. The fourth experiment, tested the vigor of Limau lime seeds in drought stress condition using PEG 6000, i.e. 0, - 0.75 bar, -1.5 bar, and -2.25 bar. The result of the first experiment showed that the treatments had no significantly different effect on all variables observed except for the seed moisture content. The second experiment revealed that the best germination media was elucidated from sand treatment and sand: soil (1:1) with the first and the second count at 20th and 29th day respectively. The result of the third and four experiment elucidated that the higher concentration of NaCl (Salinity stress condition) or PEG 6000 (drought stress condition), the smaller the germination percentage of Limau Lime’s seeds.